2021
DOI: 10.48550/arxiv.2102.08393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Figuring Out Gas & Galaxies In Enzo (FOGGIE) V: The Virial Temperature Does Not Describe Gas in a Virialized Galaxy Halo

Cassandra Lochhaas,
Jason Tumlinson,
Brian W. O'Shea
et al.

Abstract: The classical definition of the virial temperature of a galaxy halo excludes a fundamental contribution to the energy partition of the halo: the kinetic energy of non-thermal gas motions. Using simulations from the FOGGIE project (Figuring Out Gas & Galaxies In Enzo) that are optimized to resolve lowdensity gas, we show that the kinetic energy of non-thermal motions is roughly equal to the energy of thermal motions. The simulated FOGGIE halos have ∼ 2× lower bulk temperatures than expected from a classical vir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Our analysis uses the z = 2, 2.5, and 3 outputs for each of the six FOGGIE halos. As presented in Simons et al (2020), these halos are selected to be "Milky Way-like" in that they are roughly ∼ 10 12 M at z = 0 and have no mergers of mass ratios more than 1:10 after z = 2 (see also Zheng et al 2020 andLochhaas et al 2021 for the full histories and z = 0 properties of the Tempest, Squall, and Maelstrom halos). While the KODIAQ-Z absorbers are not selected to be associated with Milky Way-like halos, galaxy halos of this size account for most of the stellar mass in the universe and therefore most of the chemical enrichment.…”
Section: Motivation and Methodologymentioning
confidence: 99%
“…Our analysis uses the z = 2, 2.5, and 3 outputs for each of the six FOGGIE halos. As presented in Simons et al (2020), these halos are selected to be "Milky Way-like" in that they are roughly ∼ 10 12 M at z = 0 and have no mergers of mass ratios more than 1:10 after z = 2 (see also Zheng et al 2020 andLochhaas et al 2021 for the full histories and z = 0 properties of the Tempest, Squall, and Maelstrom halos). While the KODIAQ-Z absorbers are not selected to be associated with Milky Way-like halos, galaxy halos of this size account for most of the stellar mass in the universe and therefore most of the chemical enrichment.…”
Section: Motivation and Methodologymentioning
confidence: 99%
“…This is why the mass of peak N O VI R200c in the Voit (2019) model is at greater masses than is observed: the mass of T O VI gas is greater around galaxies with T 200c > T O VI than around galaxies with T 200c ≈ T O VI . An analysis of CGM temperatures in high resolution hydrodynamic simulations by Lochhaas et al (2021) finds a similar result: even in virialized galaxy-scale halos, gas on the outskirts of the CGM (i.e., where much of the mass resides) has a characteristic temperature of about 1/2T 200c , rather than T 200c . Halos in which some of the assembly energy is still in the form of coherent, nonthermal motions have an even lower characteristic temperature.…”
Section: What Conditions Does O VI Trace?mentioning
confidence: 78%
“…This appears to apply all the way from the CGM to the IGrM to the ICM of massive clusters, although the scatter becomes larger with decreasing halo mass. Recently, Lochhaas et al (2021) confirmed for an individual halo that the turbulent energy is a nearly constant fraction of the thermal energy over time.…”
Section: Discussionmentioning
confidence: 96%